Triglyceride-Glucose Index and Homeostasis Model Assessment-Insulin Resistance in Young Adulthood and Risk of Incident Congestive Heart Failure in Midlife: The Coronary Artery Risk Development in Young Adults Study - Zeng, Xianghui; Han, Dunzheng; Zhou, Haobin; Xue, Yuting; Wang, Xiao; Zhan, Qiong; Bai, Yujia; Huang, Xingfu; Zeng, Qingchun; Zhang, Hao; Ma, Zhuang; Ren, Hao; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective: The aim of this study was to assess the association between triglyceride-glucose (TyG) index / homeostasis model assessment-insulin resistance (HOMA-IR) within young adults and congestive heart failure (CHF), and to explore whether TyG index can replace HOMA-IR as a surrogate marker for insulin resistance in predicting the risk of CHF. Methods：A total of 4992 participants between the ages of 18 and 30 were enrolled from the Coronary Artery Risk Development in Young Adults (CARDIA) investigation (from 1985 to 1986 [year 0]). Cox proportional hazard regression analysis was conducted for assessing correlations between baseline TyG index / HOMA-IR and congestive heart failure events, together with Receiver Operating Characteristic (ROC) Curve employed for scrutinizing TyG index / HOMA-IR and he risk of CHF. Results: During the 31-year follow-up period, 64 (1.3%) out of the 4992 participants developed CHF. In multivariable Cox proportional hazards models, adjusted for confounding factors for CHF, increased risk of CHF was associated with per-unit increase in TyG index (hazard ratio [HR] 2.8; 95% confidence interval [CI], 1.7-4.7) and HOMA-IR (HR 1.2; 95%CI, 1.1-1.3). Kaplan-Meier curve analysis showed that participants in the TyG index and HOMA-IR index Q4 group had a higher risk of congestive heart failure than those in the Q1 group. The area under curve (AUC) for TyG index and HOMA-IR consisted of 0.67 (95% CI, 0.6-0.742) and 0.675 (95%CI, 0.604-0.746), respectively. There were no significant differences between TyG index and HOMA-IR for AUC (P = 0.986). Conclusions: Higher TyG index and HOMA-IR are independent risk factors for CHF. The TyG index can replace HOMA-IR in young adulthood as a surrogate marker for IR to predict the risk of CHF.